IFAS Community Development: The Importance of Local Community Action in Shaping Development - Mark A. Brennan (EDIS)
This paper is part of a series of discussions on community development. This series will include specialized papers on civic engagement, community action, and other topics important to the development of community. This document is FCS 9209, of a series of the Department of Family, Youth and Community Sciences, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2005.